Model Peningkatan Mutu Pendidikan Sekolah Dasar Berbasis Kultur Sekolah Untuk Mewujudkan Sekolah Efektif - Mukti Tri Atmaja; Vina Fithriana Wibisono; Ahmad Jalaludin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In facing various challenges and competition in schools, it is necessary to involve all components/citizens of the school in order to build relationships or partnerships with other institutions in improving the quality of education in the school. Efforts to improve and improve the quality or quality of primary school education need to be through an effective school culture. Because improving the quality of primary school education cannot be separated from the basis of school culture. Based on this culture, principals, teachers, students, and parents will feel a sense of belonging, so that they will maintain, improve, and strive for the realization of improving the quality of school education. The purpose of this study is to develop a model for improving the quality of primary school education based on school culture to create an effective school. This study uses a descriptive qualitative approach that occurs at SDN Kepuhteluk II Gresik. This qualitative data was obtained and analyzed from the results of interviews, observations and school documentation to support the conclusions of the study. The subjects in this study involved teaching and learning activities for teachers and students at SDN Kepuhteluk II Gresik. The results of this study indicate that the model used at SDN Kepuhteluk II Gresik in improving the quality of basic education based on school culture is a reform model. Efforts to improve the quality of school education at SDN Kepuhteluk II Gresik have been carried out with various school reforms related to various dimensions, such as the dimensions of the principal, the dimensions of teachers, the dimensions of students, the dimensions of parents, and the dimensions of stakeholders. As for efforts to improve and improve a quality or school quality seen from the aspect of honesty. Apart from being honest, other core values that are instilled in the students of SDN Kepuhteluk II Gresik are discipline, responsibility, patience, humility and tolerance.